German and English : academic usage and academic translation - Siepmann, Dirk, 1966- (London ; New York : Routledge, 2020)
"German and English: Academic Usage and Academic Translation focuses on academic and popular scientific/academic usage. This books brief is both theoretical and practical: on the theoretical side, it aims to provide a systematic, corpus-based account of current academic usage in English and German as well as of the translation problems associated with various academic genres; on the practical side, it seeks to equip academic translators with the skills required to produce target-language text in accordance with disciplinary conventions. The main perspective taken is that of a translator working from German into English, but the converse direction is also regularly taken into account. Most of the examples used are based on errors which occurred in real-life translation jobs. Additional practice materials and sample translations are available as eResources here: www.routledge.com/9780367619022. An important resource for professionals aspiring to translate academic texts, linguists interested in academic usage, translation scholars, graduate and post-graduate students"--
OCLC-licensed vendor bibliographic record.
Keywords: German language -- Translating into English; Academic writing -- Translating; Academic writing; German language -- Grammar, Comparative -- English; English language -- Grammar, Comparative -- German; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / German; LANGUAGE ARTS & DISCIPLINES / Journalism